(untitled) (TEST Ticontre. Theory Text Translation, 2024)
This article investigates Gianni Celati and Lino Gabellone’s translation of Entretiens avec le professeur Y, a pamphlet written by Louis-Ferdinand Céline and published by Gallimard in 1955. After posing Céline’s work within Modernism and singling out the main peculiarities of Céline’s writing, this paper presents a series of examples of the strategies adopted by the two Italian translators. Among the Celinian features identified as specifically Modernist and representing a demanding translation challenge, Céline’s transformation of the narrator into a locuteur stands out. The analysis of some excerpts from the translation will show how, both on the lexical (thanks to adoption of a septentrional koiné) and on the discursive level (thanks to the performative nature of the translating act), the two translators succeeded in reproducing the narration of the locuteur and the characteristics of Céline’s agitated prose. Questo articolo prende in esame la traduzione da parte di Gianni Celati e Lino Gabellone di Entretiens avec le professeur Y, pamphlet scritto da Louis-Ferdinand Céline e pubblicato dalla casa editrice Gallimard nel 1955. Dopo un’iniziale contestualizzazione dell’opera di Céline all’interno del movimento modernista e una ricostruzione delle principali particolarità della scrittura celiniana, il contributo presenta una serie di esempi delle strategie adottate dai due traduttori italiani. Tra le marche celiniane riconosciute come più propriamente moderniste, e che rappresentano un’impegnativa sfida traduttiva, spicca la trasformazione attuata da Céline del narratore in locuteur. Nell’analisi di alcuni estratti della traduzione, emergerà come, tanto sul piano lessicale (grazie all’adozione di una koiné settentrionale) quanto su quello della resa dialogica (grazie alla performatività dell’atto traduttivo), i due traduttori siano riusciti a dare corpo alla narrazione del locuteur e riprodurre le caratteristiche dell’agitata prosa celiniana.